THE USE OF BOARD RACE GAME AS AN ALTERNATIVE STRATEGY IN MASTERING VOCABULARY - Muhaimin, Ahmad; Samtidar, Samtidar; Ariyani, Amra (Universitas Negeri Makassar, 2023)
This study aims to determine the use of the Board Race Game as an alternative strategy to improve students' vocabulary mastery in learning English. This study used a pre-experimental approach with a total sample of 33 students of class VIII A at SMPN 4 Sungguminasa. In this study, data collection was carried out by conducting pre-test and post-test. The results of the data analysis showed that the use of the Board Race Game as an alternative strategy can improve students' vocabulary mastery. This can be proven by the t-test value lower than P (0.000 < 0.05) which means that H0 of this study is rejected and H1 is accepted. So, it can be concluded that the use of Board Race Game can improve students' vocabulary in class VIII A at SMPN 4 Sungguminasa.